A Practical Guide on Data Analysis: using EViews - Ezie, Obumneke (Kaduna, Nigeria, 2022)
The book is divided into eleven chapters. Chapters 1 to 5 constitute introduction to EViews, Descriptive, Correlation and Graphical Analysis; Estimating Single Equations; Residual Diagnostic Tests; Unit Root, Cointegration and Causality Tests using EViews; while chapters 6 to 11 contain, the Long Run Model and Error Correlation Model (ECM); Hypothesis testing using Wald -Test; Estimating a Cointegrating Regression; Multivariate Models - VAR, VECM and TODA - YAMAMOTO; Panel Data Regression and; Univariate Volatility Modelling Procedure Using EViews.
Includes bibliographical references.
osc 15/02/2024
Loans
Keywords: Econometrics